FACE FITNESS : Simple Exercises and Rituals for Toned, Glowing Skin - San Pedro, Patricia, (Founder of Sunina Skin); Gul, Maria Ines (San Francisco : CHRONICLE BOOKS, 2021)
Take your skin care to the next level with this guide to toning, sculpting, and strengthening your skin using simple, natural techniques. Within these pages, you'll discover facial stretches, massage exercises, meditative affirmations, and clean beauty tips from industry experts that will instantly rejuvenate your complexion. The 50 easy-to-follow exercises range from the Cheekbone Press for a rosy glow to the Bright Eyes to reduce puffiness and the Jawline Squeeze to ease tension. Ultimately, "Face Fitness" is not about looking a certain age, rather, it's about elevating your mindset, enhancing your inner glow, and radiating that outward to present the most beautiful you!
Includes index.
Keywords: Face -- Care and hygiene; Skin -- Care and hygiene; Facial exercises